Evaluation of TiO2 sensitized with cobalt trimer dyes as photocatalyst for water-splitting hydrogen production - Camacho Ureña, Daniela (2024)
In this research, sensitized TiO2 photocatalysts were synthesized based on the functionalization of their surface with organic molecules (glycine and aminocaproic acid) and a cobalt trimer in its molecular form [Co3(dpa)4Cl2], (dpa = 2,2'-dipyridylamine), using two different heating methods (reflux and microwave) to carry out the anchoring reactions. The capacities of the photocatalysts for producing hydrogen from the water-splitting reaction were evaluated using a medium-pressure Hg lamp (125 W) and methanol as a sacrificial agent. Also, CuO-TiO2 and CoO-TiO2 photocatalysts were synthesized and evaluated for comparison purposes. The photocatalyst that presented the best performance was TiO2 sensitized with the cobalt trimer, using glycine as an anchoring molecule, and prepared with microwave heating; this photocatalyst generated hydrogen at an average rate of 1887 mmol g-1 h-1. It was observed that the chain length of the anchoring molecule affects the photocatalytic activity, as the chain length increases, the production of hydrogen decreases. Last, microwave heating produced the photocatalyst with the best performance on hydrogen generation.